A self-organized structure for mobility management in wireless networks. (November 2015) - Smys, S.; Raj, Jennifer S.
Abstract: The objective of this work is to analyse performance of unstable mobile nodes with self-organization structures in Delay Tolerant Networks (DTN). This process enables the nodes to utilize their power fairly, and ensures that the links are established between nodes and used to improve the connectivity. In this paper two approaches are proposed: 1. Self-Healing (SH) and 2. Unstable Topology Structure (UTS) approaches based on localized computations. The proposed work is proven with simulations by analysing node degree, coverage area and Quality of Service (QoS) parameters. The performance of the work is analysed in a network simulator with mathematical models.